Clinicopathological molecular characterizations of sinonasal NUT carcinoma: a report of two cases and a literature review - Chen, Min; Li, Shuang; Jiang, Lili (Frontiers in Oncology, 2024)
Nuclear protein in testis (NUT) carcinoma (NC) is a rare, aggressive tumor with a typical NUTM1 gene rearrangement. Herein, we report a series of 2 cases of sinonasal NC: one in a 16-year-old woman and one in a 37-year-old man. Immunohistochemistry (IHC) staining for NUT (C52B1), fluorescence in situ hybridization (FISH), and next generation sequencing (NGS) sequencing were performed to investigate the morphological and genetic features of sinonasal NC. The two cases presented similar pathological features and IHC markers, and typical morphological changes, including undifferentiated cells and abrupt keratinization, were observed, with numerous mitotic figures and widespread tumor necrosis.Diffuse expression of NUT, CK, p63, and p40 was noted, while the tumors were negative for synaptophysin, chromogranin A, S-100, EBV-ISH, and PD-L1. Both tumors harbored a NUTM1 rearrangement. Subsequent sequencing revealed a rare BRD3::NUTM1 fusion and a classic BRD4::NUTM1 fusion. In addition, MCL1 copy number gain (2.1), low tumor mutation burden and stable microsatellites, were also confirmed. Case 1 received surgery and chemoradiotherapy but died 13 months after local recurrence and subsequent lung and bone metastasis. Case 2 underwent chemoradiotherapy and unfortunately died from the disease 6 months later. A review of all previously reported cases of sinonasal NCs (n=55) revealed that these tumors occur more frequently in female pediatric patients (n=11, male: female =3:8), whereas this sex difference is not observed in adult patients (n=44, male: female =23:21).The median survival times of pediatric and adult patients were 17 and 13.8 months, respectively.